KEANEKARAGAMAN CAPUNG (ORDO: ODONATA) DI KAWASAN WISATA SEMARA RATIH DESA TARO, GIANYAR-BALI - Tresia Uliani Purba; Ni Made Suartini; Ni Luh Watiniasih (SIMBIOSIS, 2024)
Dragonfly is an insect with an interesting morphology and is often found in areas that are still beautiful and unpolluted, making it an environmental bioindicator.. This research was conducted to determine the diversity of dragonfly species and environmental factors that could influence their existence. The study was carried out in January-February 2023 using the exploratory method. Samples were taken from three station points in the morning and evening five times. The captured dragonfly samples were then identified by observing their morphological characters such as body shape, color pattern on the thorax and abdomen, wing venation, and wing color pattern. Environmental factors of temperature, humidity and altitude where measured every sampling site. The results obtain ten species of dragonflies were found, namely Copera marginipes, Agriocnemis pygmaea, Agriocnemis femina, Ischnura senegalensis, Orthetrum testaceum, Orthetrum sabina, Potamarcha congener, Neurothemis ramburii, Neurothemis terminata. The diversity index obtained was in the medium category with almost even distribution and no dominating species were found. Environmental conditions support the existence of dragonflies in Semara Ratih, Taro Tourism Village, Gianyar-Bali so that in the future it can be used as a tourist attraction in the area. Keywords: dragonfly, identification, morphological characters, habitat, Taro